Social support and avoidance mediate positive and negative effects of emotion recognition ability on mental health in medical students - Nils R. Sommer; Valerie Carrard; Céline Bourquin; Alexandre Berney; Katja Schlegel (Scientific Reports)
Abstract The ability to recognize others’ feelings from nonverbal expressions, known as emotion recognition ability (ERA), is considered a crucial socio-emotional competence that may enhance both intra- and interpersonal functioning in healthcare professionals. However, evidence for its association with mental health is mixed. The present longitudinal study examined whether medical students with higher ERA scores report better mental health over one year and whether this effect is mediated by a higher perceived availability of social support. Longitudinal mediation analyses were conducted with data from 986 medical students in Switzerland who completed questionnaires at two time points, one year apart. While ERA at T1 was not directly associated with mental health issues and burnout at T2, it predicted greater social support availability at T2, which in turn predicted fewer mental health issues and lower burnout. Exploratory analyses revealed that although ERA increased social support, it also predicted higher habitual avoidance coping, which was negatively related to mental health. Overall, this study sheds light on both positive and negative indirect pathways through which ERA may affect mental health in future healthcare professionals. These insights highlight the need for careful consideration of ERA intervention studies, addressing both positive and negative influences on mental health.